LAA Thrombus and Stroke From Surgical LAA Closure Failure From Suture Insufficiency Treated With LAAO - Vladyslav Kavalerchyk, MD; Stephan Stöbe, MD; Andreas Hagendorff, MD; Torsten Doenst, MD; Ritu Thamman, MD (JACC: Case Reports)
Background: Left atrial appendage (LAA) occlusion (LAAO) is used to prevent thromboembolic events in high stroke risk patients. However, surgical LAA closure can fail, resulting in residual flow and thrombus formation. Case Summary: A 77-year-old man with a history of bioprosthetic valve replacements and prophylactic LAA closure presented with dizziness. Brain magnetic resonance imaging showed microembolic infarcts, and transesophageal echocardiography revealed suture insufficiency with LAA thrombus. Given the patient’s preference to avoid long-term anticoagulation, an Amplatzer device was used for LAAO. Postprocedural transesophageal echocardiography confirmed successful occlusion, and the patient remained stroke free on aspirin alone on follow-up. Discussion: This case highlights the limitations of surgical LAA closure and the role of LAAO as an alternative treatment to mitigate thromboembolic risk in high-risk patients. It underscores the importance of accurate imaging in therapy planning. Take-Home Message: LAAO offers a viable option for patients with failed surgical LAA closure, balancing stroke prevention with bleeding risk.